Expanded ACE2 dependencies of diverse SARS-like coronavirus receptor binding domains. - Sarah M Roelle; Nidhi Shukla; Anh T Pham; Anna M Bruchez; Kenneth A Matreyek (PLoS Biology, 2022)
Viral spillover from animal reservoirs can trigger public health crises and cripple the world economy. Knowing which viruses are primed for zoonotic transmission can focus surveillance efforts and mitigation strategies for future pandemics. Successful engagement of receptor protein orthologs is necessary during cross-species transmission. The clade 1 sarbecoviruses including Severe Acute Respiratory Syndrome-related Coronavirus (SARS-CoV) and SARS-CoV-2 enter cells via engagement of angiotensin converting enzyme-2 (ACE2), while the receptor for clade 2 and clade 3 remains largely uncharacterized. We developed a mixed cell pseudotyped virus infection assay to determine whether various clades 2 and 3 sarbecovirus spike proteins can enter HEK 293T cells expressing human or Rhinolophus horseshoe bat ACE2 proteins. The receptor binding domains from BtKY72 and Khosta-2 used human ACE2 for entry, while BtKY72 and Khosta-1 exhibited widespread use of diverse rhinolophid ACE2s. A lysine at ACE2 position 31 appeared to be a major determinant of the inability of these RBDs to use a certain ACE2 sequence. The ACE2 protein from Rhinolophus alcyone engaged all known clade 3 and clade 1 receptor binding domains. We observed little use of Rhinolophus ACE2 orthologs by the clade 2 viruses, supporting the likely use of a separate, unknown receptor. Our results suggest that clade 3 sarbecoviruses from Africa and Europe use Rhinolophus ACE2 for entry, and their spike proteins appear primed to contribute to zoonosis under the right conditions.